Estimating Residential Demand for Water in Kuwait: A Cointegration Analysis - Alfalah, Osama (International Journal of Energy Economics and Policy, 2021)
This paper aims to investigate the determinants of water demand in Kuwait and assess their impact on consumption. To do this, we applied the cointegration regression and the error correction model (ECM) on annual time series data, covering the period from 1972 to 2019. We found that the price elasticity for fresh water demand in Kuwait is negative and elastic in the long run (-1.095), which is consistent with the existing literature. Also, we found that the income elasticity for demand was positive in the long run (0.234), however, no short run effect was found for either price or income. Our results suggest that policymakers should expect a long run impact when using water prices to adjust the consumption behavior in Kuwait. Keywords: Development, Structural Time Series Model, Energy Prices, Water Demand, Subsidies. JEL Classifications: H20, Q25, L16, Q41 DOI: https://doi.org/10.32479/ijeep.11317